Implementation of the Integration of the Inquiry Learning Model Based on Digital Storytelling in Arabic Language Learning - Samsiah Nur Susan; Fitri Mawaddah bako; Nur Azizah Bancin; Abdur Rahman Purba (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe: 1) the integration of the inquiry learning model in Arabic language learning based on digital storytelling; 2) the effect of implementing the digital storytelling-based inquiry model on Arabic language skills and critical thinking skills; 3) student responses to Arabic language learning that integrates the inquiry model with video storytelling. The study was conducted at Al Umm Smart Center Junior High School, Tembung, in the even semester of the 2025/2026 academic year. The study population was 63 eighth-grade students. A sample of 30 students was selected using a purposive sampling technique. The research instruments used included observation sheets, student response questionnaires, interview guidelines, and speaking and listening skill tests. In addition, documentation in the form of student assignments was also used as supporting data. Data analysis used a descriptive qualitative approach through data reduction, data analysis, and conclusion drawing. Research results: 1) Integrating the inquiry model into digital storytelling-based Arabic language learning can improve student engagement, critical thinking skills, and Arabic listening skills (maharah istima') and speaking skills (maharah kalam); 2) The digital storytelling-based inquiry model impacts Arabic language skills and critical thinking skills; 3) positive responses to the use of video storytelling media are seen as engaging, contextual, and facilitate understanding of the material.